Diagnostic yield and clinical effects of exome sequencing analysis in patients with early-onset scoliosis. Issue 1 (October 2019) - Zhao, Sen; Zhang, Yuanqiang; Chen, Weisheng; Wang, Shengru; Liu, Pengfei; Zhang, Shuyang; Wise, Carol A; Lupski, James R; ,; Wu, Zhihong; Qiu, Guixing; Zhang, Jianguo; et al.
Abstract: Background: Scoliosis is clinically defined as a spine deformity with lateral curvature greater than 10° and the cause of the disease is elusive. Early onset scoliosis, defined by an onset age before 10 years, conveys a substantial health risk to affected children. Although exome sequencing has emerged as a first-line diagnostic method for rare diseases, genetic testing is not routinely done for children with early onset scoliosis. We aimed to explore the diagnostic yield of exome sequencing in patients with early onset scoliosis. Methods: We recruited a Chinese cohort of patients who were clinically diagnosed with early onset scoliosis through the Deciphering disorders Involving Scoliosis and COmorbidities (DISCO). We did exome sequencing on these individuals and available family members. Exome sequencing data were interpreted according to the American College of Medical Genetics and Genomics guidelines. Patients were followed up for a minimum of 2 years. We also recruited an American cohort of 13 patients with clinically diagnosed idiopathic early onset scoliosis, who underwent exome sequencing. Findings: We recruited 447 patients in the Chinese cohort and 323 (72%) of 447 patients with early onset scoliosis were followed up for a minimum of 2 years. In the Chinese cohort, we detected diagnostic variants in 92 (21%) of 447 patients with early onset scoliosis, encompassing 33 disease-causing genes and five genomic regions. The age at presentation, the number of organ systems involved, and the Cobb angle were the three features that were most predictive of a molecular diagnosis. Notably, 14 (41%) of 34 patients with non-TBX6-associated congenital scoliosis (TACS) molecular diagnoses had a higher post-surgery complication rate than did the 24 (9·2%) of 260 patients who were molecularly undiagnosed (p=0·000008). In the American cohort, one (8%) of 13 patients had a molecular diagnosis of Sotos syndrome, making the total number of patients in whom we found diagnostic variants 93 (20·2%) of 460. Interpretation: Exome sequencing could identify the genetic cause in patients with early onset scoliosis. Specific clinical features and feature pairs provided indications for genetic testing in these patients. The prevention of post-surgery complications could potentially be implemented for patients with a non-TACS molecular diagnosis. Funding: National Natural Science Foundation of China, Beijing Natural Science Foundation, 2016 Milstein Medical Asian American Partnership Foundation Fellowship Award in Translational Medicine, CAMS Initiative Fund for Medical Sciences, the Central Level Public Interest Program for Scientific Research Institute, the National Key Research and Development Program of China, the National Undergraduates Innovation and Training Program of Peking Union Medical College, US National Institutes of Health, National Institute of Neurological Disorders and Stroke, National Human Genome Research Institute and National Heart, Lung, and Blood Institute, the National Human Genome Research Institute, TX Scottish Rite Hospital Research Fund, Foundation Cotrel, and P01 HD084387.